System Prediction Production PT.Vico Indonesia Using Method Holt Winters - Riyan Sukma Sasongko; Eko Prasetyo; Rani Purbaningtyas (Fakultas Teknik Universitas Bhayangkara, 2017)
Problem that Taken in this study is the process of forecasting oil and gas production in accordance so that companiescan know the prediction of the amount of oil and gas in the future. The method used to determine production predictionis Holt-Winters forecasting method. In testing the system will do the comparison of alpha, beta and gamma. Using thealpha value = 0.2, beta = 0.1 and gamma 0.5 to get better multiplicative forecast for oil and gas data. And to get thesmaller error difference compared to the smaller alpha (α), beta (β) and gamma (γ) then the smaller the differencewill be. The Multiplexative Spring Method and the Seasonal Additive Method are good enough for oil and gasproduction data